How to interpret liver function tests - Christina Levick (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2017)
Careful interpretation of liver function tests within the clinical context can help elucidate the cause and severity of the underlying pathology. Predominantly raised alkaline phosphatase represents the cholestatic pattern of biliary pathology, whilst predominantly raised alanine aminotransferase and aspartate aminotransferase represent the hepatocellular pattern of hepatocellular pathology. The severity of liver dysfunction or biliary obstruction is reflected in the bilirubin level and the degree of liver synthetic function can also be indicated by the albumin level. Beyond the liver function tests, prothrombin time provides another marker of liver synthetic function and a low platelet count suggests portal hypertension.